Diesel soot combustion over ceria catalyst: Evolution of functional groups on soot surfaces. (15th April 2023) - Wei, Jiangjun; Fan, Chenyang; Zhuang, Yuan; Fu, Zheng; Guan, Ze; Li, Haizhao; Li, Deliang; Qian, Yejian
Highlights: Effect of ceria on soot oxidation was explained by functional groups on soot surfaces. Reactions between ceria lattice oxygen and soot occur during <500℃ thermal annealing. Thermal annealing yields increases in larger CO groups and defects on soot surface. Ceria enhances amorphous C consumption and sp 3 generation at initial oxidation phase. Abstract: The use of ceria catalyst is a common way to promote the soot combustion during DPF regeneration, due to the superior capability to store and release oxygen. In this work, the oxidation behavior and evolutions of surface functional groups have been critically discussed to reveal the mechanism of soot catalytical oxidation, based on the results derived from temperature-programmed-oxidation (TPO) experiments, X-ray photoelectron spectroscopy, Fourier Transfer Inferred spectrometer, and Raman scattering spectrometer. Before the TPO test, the soot samples with and without ceria were annealed at up to 500℃ in pure N2 gas. During the thermal annealing, the reaction between soot and desorbed lattice oxygen in ceria leads to damage of the graphitic network and proliferation of the strongly oxidized OCO groups, defects, and disorder structure on soot surface. In consequence, the onset temperature for the mixture of diesel soot and ceria in loose-contact condition slightly elevates than the pure diesel soot. At initial soot catalytical oxidation, ceria enhances the consumption of amorphous carbon and generation of sp 3 hybridized carbon. As the oxidation process evolves, ceria gives a boost to the complete saturation of C vacancy and the generation of larger O groups on soot surfaces. Meanwhile, the damage of the PAHs matrix occurs with the assistant of ceria catalyst, probably by facilitating the O desorption on the basal-plane C atoms. All these differences induced by ceria facilitate the oxidation reactions in the subsequent phases.